The cancer patient and cardiology. (2nd October 2020) - Zamorano, José Luis; Gottfridsson, Christer; Asteggiano, Riccardo; Atar, Dan; Badimon, Lina; Bax, Jeroen J.; Cardinale, Daniela; Cardone, Antonella; Feijen, Elizabeth A.M.; Ferdinandy, Péter; López‐Fernández, Teresa; Gale, Chris P.; et al.
Abstract: Advances in cancer treatments have improved clinical outcomes, leading to an increasing population of cancer survivors. However, this success is associated with high rates of short‐ and long‐term cardiovascular (CV) toxicities. The number and variety of cancer drugs and CV toxicity types make long‐term care a complex undertaking. This requires a multidisciplinary approach that includes expertise in oncology, cardiology and other related specialties, and has led to the development of the cardio‐oncology subspecialty. This paper aims to provide an overview of the main adverse events, risk assessment and risk mitigation strategies, early diagnosis, medical and complementary strategies for prevention and management, and long‐term follow‐up strategies for patients at risk of cancer therapy‐related cardiotoxicities. Research to better define strategies for early identification, follow‐up and management is highly necessary. Although the academic cardio‐oncology community may be the best vehicle to foster awareness and research in this field, additional stakeholders (industry, government agencies and patient organizations) must be involved to facilitate cross‐discipline interactions and help in the design and funding of cardio‐oncology trials. The overarching goals of cardio‐oncology are to assist clinicians in providing optimal care for patients with cancer and cancer survivors, to provide insight into future areas of research and to search for collaborations with industry, funding bodies and patient advocates. However, many unmet needs remain. This document is the product of brainstorming presentations and active discussions held at the Cardiovascular Round Table workshop organized in January 2020 by the European Society of Cardiology. Abstract : Many cancer drugs lead to a variety of cardiovascular toxicities. Management begins with risk stratification and mitigation/prevention strategies such as pharmacological, exercise, and other lifestyle interventions.